2014
DOI: 10.3892/etm.2014.1900
|View full text |Cite
|
Sign up to set email alerts
|

Emodin inhibits LOVO colorectal cancer cell proliferation via the regulation of the Bcl-2/Bax ratio and cytochrome c

Abstract: In this study, the effect of emodin and its mechanism of action were investigated in LOVO colorectal cancer cells. Cell growth was determined using a Cell Counting kit-8 assay, and the results demonstrated that emodin significantly inhibited the growth of LOVO cells in a concentration-dependent manner. In order to investigate the anticancer mechanism of emodin, reverse transcription polymerase chain reaction assays were performed to determine the B-cell lymphoma-2 (Bcl-2)/Bcl-2-associated X protein (Bax) expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 18 publications
(16 reference statements)
2
27
0
Order By: Relevance
“…These observations demonstrate that emodin-induced apoptosis of Bcap-37 and ZR-75-30 cells was triggered by the downregulation of Bcl-2 and the upregulation of Bax. Previous studies have demonstrated that the mitochondrial membrane potential stimulates the opening of the mitochondrial membrane, resulting in the release of cytochrome c into the cytoplasm, caspase activation and degradation of key intracellular proteins, which leads to apoptosis (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…These observations demonstrate that emodin-induced apoptosis of Bcap-37 and ZR-75-30 cells was triggered by the downregulation of Bcl-2 and the upregulation of Bax. Previous studies have demonstrated that the mitochondrial membrane potential stimulates the opening of the mitochondrial membrane, resulting in the release of cytochrome c into the cytoplasm, caspase activation and degradation of key intracellular proteins, which leads to apoptosis (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 and Bax proteins are members of the Bcl family of proteins (13,14). A number of studies have reported that the Bcl-2 family proteins participate in AD, and are associated with cell apoptosis (15,16).…”
Section: B Amentioning
confidence: 99%
“…Among these, many of the medicines derive from Traditional Chinese Medicine (TCM) and have been confirmed to be effective in the treatment of a number of tumors via targeting and regulating multiple molecular pathways (5,6). Emodin is an active ingredient derived from root and rhizome of Rheum palmatum L, which is a plant widely used in Chinese medicine as a laxative for thousands of years (7,8). The molecular formula of emodin is C 15 H 10 O 5 and its molecular weight is 270.…”
Section: Introductionmentioning
confidence: 99%